Mengukur Tingkat Usability Pengguna Online Public Access Catalog dengan Metode System Usability Scale di Perpustakaan UIN Sumatera Utara - Saragih, Rahmat Al-Rasyid; Sayekti, Retno (Tapis: Jurnal Penelitian Ilmiah, 2024)
This research aims to measure the usability level of users of the Online Public Access Catalog (OPAC) application as an information retrieval tool for users at the North Sumatra State Islamic University (UINSU) Library. Online Public Access Catalog (OPAC) is a computer-based installed catalog system that can be used by users to browse catalog data to ensure the availability of collections needed by users whether the library stores certain works to obtain information and their location in the library. The method used in this research is the System Usability Scale (SUS) which was developed by John Brooke since 1986 and SUS is a usability scale that is reliable, popular, effective and cheap. Researchers used the SUS method to measure the usability level of OPAC application users in the UINSU library by asking 10 questions to 60 users. By knowing the level of user satisfaction, we can also find out whether the application is suitable for use and running well. The results of calculations from 60 respondents were obtained by researchers using the SUS method, getting a score of 62.3, falling into the OK category and grade D. These results show that the level of satisfaction of users of the OPAC application in the UINSU library is sufficient and needs to be improved.